IMPLEMENTASI SUPERVISI AKADEMIK PENGAWAS DALAM MENINGKATKAN KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH SMA DI KABUPATEN LAMPUNG SELATAN - Nia Hafudhah; Muhammad Ihsan Dacholfany; Sutrisni Andayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of academic supervision by school supervisors in improving the instructional leadership of senior high school principals in South Lampung Regency. A qualitative descriptive approach was employed, involving supervisors, principals, and teachers from five SMA under the supervision of the regional education office. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model comprising data reduction, data presentation, and conclusion drawing. The findings reveal that the implementation of academic supervision by supervisors has been carried out through three main stages: planning, execution, and evaluation with follow-up. At the planning stage, supervisors systematically designed supervision programs, established schedules through coordination with principals, and prepared relevant supervision instruments. During execution, supervisors conducted direct observations, monitored learning processes, engaged in professional dialogues with principals, and provided technical guidance. In the evaluation and follow-up stage, supervisors delivered constructive feedback and recommendations for continuous improvement. The study also identified supporting factors, such as the commitment of supervisors and principals as well as effective communication among stakeholders, alongside inhibiting factors, including limited supervision time due to administrative burdens and varying levels of teacher competence in utilizing learning technology. The implementation of academic supervision has contributed positively to strengthening instructional leadership, particularly in goal setting, curriculum management, supervision of teachers, and professional development of educators.